Exploring the Cross-Sectional Association between Transit-Oriented Development Zoning and Active Travel and Transit Usage in the United States, 2010–2014 - Thrun, Emily; Leider, Julien; Chriqui, Jamie F. (Frontiers in Public Health, 2016)
Background: In response to traditional zoning codes that contribute to car-dependent, sprawling, and disconnected neighborhoods, communities are reforming their land use laws to create pedestrian-friendly areas that promote physical activity. One such reform is the adoption of transit-oriented developments or districts (TODs). TODs are higher-density, compact, mixed use areas located around transit stops that are designed to encourage walking. Purpose: To identify the characteristics of communities that have adopted TODs in their land use laws and examine if communities that have included TODs in their zoning codes are more likely to have adults that commute by any form of active transportation (i.e., walking, biking, or public transportation) or by using public transportation specifically. Methods: Zoning codes effective as of 2010 were obtained for a purposeful sample of the largest 3,914 municipal jurisdictions located in 473 of the most populous US counties and consolidated cities within 48 states and the District of Columbia. They were evaluated to determine whether they included TOD districts or regulations using a coding tool developed by the study team. Descriptive statistics together with t-tests and Pearson’s chi-squared independence test were used to compare characteristics of jurisdictions with and without TOD zoning. Multivariate linear regressions were used to compute the adjusted association between TOD zoning and taking public or active transportation to work. Results: Jurisdictions with TOD zoning were located more in the South and West than non-TOD jurisdictions and were more populous, higher income, more racially diverse, and younger. Jurisdictions with TOD zoning had significantly higher percentages of occupied housing with no vehicle than those without TOD zoning. TOD zoning was associated with significantly higher rates of public transportation to work (β=2.10, 95% CI=0.88, 3.32) and active transportation to work (β=2.48, 95% CI=1.03, 3.94). Conclusions: Communities that have or are considering developing public transit infrastructure may want to modify their zoning codes to include TODs to promote physical activity and active travel to work.